2020
DOI: 10.3390/c6020026
|View full text |Cite
|
Sign up to set email alerts
|

Power Cycling and Reliability Testing of Epoxy-Based Graphene Thermal Interface Materials

Abstract: We report on the lifespan evolution of thermal diffusivity and thermal conductivity in curing epoxy-based thermal interface materials with graphene fillers. The performance and reliability of graphene composites have been investigated in up to 500 power cycling measurements. The tested composites were prepared with an epoxy resin base and randomly oriented fillers consisting of a mixture of few-layer and single-layer graphene. The power cycling treatment procedure was conducted with a custom-built setup, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 79 publications
2
13
0
Order By: Relevance
“…At the loading of , the increase in thermal conductivity slows down. This trend is consistent with prior studies for noncuring graphene composites [ 41 ], and different from that observed in curing epoxy composites with graphene [ 19 , 20 , 36 , 37 , 38 , 39 , 40 , 42 ]. In the cured solid TIMs, the thermal conductivity reveals linear to super-linear dependence on the filler loading [ 39 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…At the loading of , the increase in thermal conductivity slows down. This trend is consistent with prior studies for noncuring graphene composites [ 41 ], and different from that observed in curing epoxy composites with graphene [ 19 , 20 , 36 , 37 , 38 , 39 , 40 , 42 ]. In the cured solid TIMs, the thermal conductivity reveals linear to super-linear dependence on the filler loading [ 39 ].…”
Section: Resultssupporting
confidence: 91%
“…It was also established that few-layer graphene (FLG) maintains high thermal conductivity, similar to bulk graphite owing to its smooth surface and, as a result, insignificant reduction in thermal conductivity due to the phonon—boundary scattering [ 27 , 28 , 29 , 30 ]. A mixture of single-layer graphene and FLG demonstrated the largest enhancement in the thermal conductivity of the TIM composites [ 19 , 20 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In the context of thermal research and TIMs, we will refer to the processed mixture of graphene and FLG flakes with lateral dimensions in several μm range as graphene fillers .…”
Section: Introductionmentioning
confidence: 99%
“…This group worked on a power cycled reliability study on graphene-filled epoxy TIMs, without an adjoining junction [268]. The decision to not examine the TIM inside a junction sandwich stemmed from a desire to analyze the intrinsic thermal conductivity lifespan performance and.…”
Section: Lifespan Reliability and Performancementioning
confidence: 99%
“…Unfortunately, substantial micro-filler loadings (>50 wt.%) are commonly required to endow composites with exceptional thermal conductivity exceeding 5 W/m•K and, as a result, the mechanical and processing qualities will encounter some obstacles. Although nanofillers outperform conventional fillers in terms of increasing heat conductivity at low filler concentrations (less than 10 wt.%), their agglomeration tendency at higher filler concentrations due to robust self-interaction limits their application [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of various shapes of carbon black nanoparticles was studied in [21], and it was discovered that particles with a branching shape build an electrically conductive framework more efficiently than particles with a spherical shape. The most effective construction of a conducting frame occurs as a synergistic effect of the interaction of several types of carbon filler, according to studies [17,23,24,28]. Carbon fillers have a good effect on the rheological features [23], mechanical properties [16,19,26], and fire resistance [25] of polymer composites, in addition to their electrically conductive capabilities.…”
Section: Introductionmentioning
confidence: 99%